Deconvolution of the particle size distribution of ProRoot MTA and MTA Angelus - William Nguyen Ha; Fardad Shakibaie; Bill Kahler; Laurence James Walsh (Medical Journals Sweden, 2016)
Objective Mineral trioxide aggregate (MTA) cements contain two types of particles, namely Portland cement (PC) (nominally 80% w/w) and bismuth oxide (BO) (20%). This study aims to determine the particle size distribution (PSD) of PC and BO found in MTA. Materials and methods The PSDs of ProRoot MTA (MTA-P) and MTA Angelus (MTA-A) powder were determined using laser diffraction, and compared to samples of PC (at three different particle sizes) and BO. The non-linear least squares method was used to deconvolute the PSDs into the constituents. MTA-P and MTA-A powders were also assessed with scanning electron microscopy. Results BO showed a near Gaussian distribution for particle size, with a mode distribution peak at 10.48 μm. PC samples milled to differing degrees of fineness had mode distribution peaks from 19.31 down to 4.88 μm. MTA-P had a complex PSD composed of both fine and large PC particles, with BO at an intermediate size, whereas MTA-A had only small BO particles and large PC particles. Conclusions The PSD of MTA cement products is bimodal or more complex, which has implications for understanding how particle size influences the overall properties of the material. Smaller particles may be reactive PC or unreactive radiopaque agent. Manufacturers should disclose particle size information for PC and radiopaque agents to prevent simplistic conclusions being drawn from statements of average particle size for MTA materials.